INCREASING THE ABILITY TO PROVIDE NEW SERVICES BY IMPROVING THE CASH FLOWS OF COMMERCIAL BANKS IN THE NEW UZBEKISTAN - Khojaev Erkin Normatovich; Nabiyev Farrukh Safarovich (Western European Studies, 2026)
This article analyzes the issues of expanding banking services by improving cash flow management of commercial banks in the context of New Uzbekistan. The economic essence of cash flows, their sources, and their impact on banking activities are studied. In addition, opportunities for introducing digital and innovative services through effective cash flow management are identified. Based on the research results, practical recommendations for commercial banks are proposed
Keywords: Commercial banks; cash flows; banking services